2010
DOI: 10.1089/ars.2009.2877
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Dependent Signaling Mechanisms for Hypoxic Ca2+Responses in Pulmonary Artery Myocytes

Abstract: Hypoxic exposure causes pulmonary vasoconstriction, which serves as a critical physiologic process that ensures regional alveolar ventilation and pulmonary perfusion in the lungs, but may become an essential pathologic factor leading to pulmonary hypertension. Although the molecular mechanisms underlying hypoxic pulmonary vasoconstriction and associated pulmonary hypertension are uncertain, increasing evidence indicates that hypoxia can result in a significant increase in intracellular reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 116 publications
(113 reference statements)
6
88
0
Order By: Relevance
“…Hypoxic inhibition of K + channels results in membrane depolarization, the activation of voltage-dependent Ca 2+ (Ca V ) channels, extracellular Ca 2+ influx and intracellular Ca 2+ release, thus resulting in an increase in [Ca 2+ ] i , followed by pulmonary vasoconstriction and proliferation of PASMCs [29] . Opening K + channels contributes to the regulation of hypoxic pulmonary vasoconstriction and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic inhibition of K + channels results in membrane depolarization, the activation of voltage-dependent Ca 2+ (Ca V ) channels, extracellular Ca 2+ influx and intracellular Ca 2+ release, thus resulting in an increase in [Ca 2+ ] i , followed by pulmonary vasoconstriction and proliferation of PASMCs [29] . Opening K + channels contributes to the regulation of hypoxic pulmonary vasoconstriction and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NFATc3 nuclear export is regulated by phosphorylation by several serine/threonine kinases, such as glycogen synthase kinase-3␤ and JNK1/2 (3,(33)(34)(35), and by the activity of the exportin CRM1 (3,33,35). The components of this signaling pathway, except for CRM1, have been shown to be differentially regulated by O 2 ·Ϫ and H 2 O 2 (4,5,14,17,18,40,49,53,64,71).…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide and hydrogen peroxide are kinds of ROS produced from endothelial nitric oxide (NO) synthase, NADPH oxidase, xanthine oxidase, and the mitochondrial respiratory chain as the major sources (27). It was previously demonstrated that endotheliumderived ROS mediates contraction by elevating the intracellular Ca 2+ concentration in pulmonary arterial smooth muscle (28), by activating thromboxane A 2 (TP) receptor in aorta from SHR (29), and by inhibiting endotheliumderived relaxing factor (NO) in rat aorta (30). It seems unlikely in the present study that the TP receptor is responsible for the increased contraction, since the TPreceptor blocker SQ29548 did not affect the MGO-induced enhancement of Ang II-induced contraction.…”
Section: Discussionmentioning
confidence: 99%